Otimização dos parâmetros de controle do conversor do lado do rotor de um gerador de indução duplamente alimentado utilizando evolução diferencial - Pulici, Alex Sandro Viel (2017)
This work aims to investigate and suggest improvements in the mesh responses of the rotor side converter of a wind turbine system that uses the double fed induction generator, controlled by vector control oriented by the angle of the network, aiming to increase sistem Stability. To optimize the gains of proportional and integrative controllers, a population optimization metaheuristic, called differential evolution, is used where, 25 operating points of the system will be used in the design stage to tune efficient controllers regardless of system conditions. The behavior of the control meshes are evaluated after the occurrence of three-phase faults, using the MATLAB / Simulink® environment.